Quantitative risk assessment for aflatoxin M1 associated with the consumption of milk and traditional dairy products in Argentina - Costamagna, D. (2021)
A quantitative risk assessment for exposure to aflatoxin M1 (AFM1) related to the consumption of milk and traditional dairy products of Argentina was developed. The frequency and concentration of AFM1 was modelled at various stages through the milk processes, considering Argentinean practices. Concentration of AFM1 (0.046 μg/l, 95%CI = 0.002?0.264 μg/l) in raw milk was estimated. The AFM1 concentration in milk was sensitive to the carry-over rate (r = 0.80), and milk yield in the first third of lactation during the spring?summer season (r = 0.11). AFB1 levels in silage (r = 0.22), pasture during the spring?summer season (r = 0.11), concentrate (r = 0.08), and cotton seed (r = 0.05) were the factors most correlated with AFM1 concentrations. Although the results showed that MoE values for the mean and median exposure to AFM1 were < 10,000 in infants, toddlers, and other children, the additional cancer risk due to exposure to AFM1 in infants, toddlers, and other children was 0.007, 0.005, and 0.0009 additional cases per year per 100,000 individuals, respectively, which indicates no health concern. In addition, the percentages of the population exceeding HI values (HI > 1) for exposure to AFM1 for infants, toddlers, and other children were 45%, 49.1%, and 40.6%, respectively. Under this scenario, the most susceptible population at risk was children < 10 years old; therefore, it is necessary to establish measures to prevent contamination of AFM1 in milk and milk products.